Educational innovation in engineering - Gómez Cano, Carlos Alberto (2024)
Currently, supporting educational transformation processes, with the conscious incorporation of technologies, but also in correspondence with the development of individuals and society itself, entails an important challenge for educational systems. In the area of engineering, precisely because of its direct contribution to the improvement of invention processes, both in academia and industry, this preparation to assume new trends in educational innovation is transcendental. Therefore, the objective of the research was to analyze the scientific production on educational innovation in the area of engineering in the period 2019 - 2023. A bibliometric study was implemented accompanied by the triangulation of the main results, which was executed on the basis of SCOPUS data. A homogeneous and increasing trend was identified during the period. Among the areas of knowledge that stood out the most, followed by engineering, were computer sciences, social sciences and energy. In general, educational innovation faces great challenges, among them, the diversification of areas, the proliferation of experiences and the construction of new processes based on what was learned during the pandemic.